Evaluating universal primary education in Uganda: School fee abolition and educational outcomes - Sophia Kan; Stephan Klasen (Review of Development Economics, 2021)
This paper analyzes the effect of lifting primary school fees on educational attainment in Uganda. After the abolishment of school fees in 1997, the enrollment rate more than doubled. Two decades later, we know little about the effect of the policy on educational attainment. With recent data on eight cohorts exposed to free education, we analyze the impact of the policy on years of completed primary school, completion of primary school, and transitioning to secondary school. We use a straightforward regression analysis with cohort dummies and household fixed effects to control for unobserved heterogeneity. We find that lifting school fees had no effect on the years of primary school achievement and the likelihood of primary school completion. We find some weak evidence that the likelihood of those who completed primary education to start secondary school increased after Universal Primary Education.
Keywords: 330; international education development; school fees; Uganda; UPE